2012
DOI: 10.5796/electrochemistry.80.759
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Carbon Source on the Surface and Electrochemical Characteristics of Lithium Excess Li4.3Ti5O12 Carbon Composite

Abstract: We have investigated the preparation and electrochemical characteristics of a lithium excess Li 4.3 Ti 5 O 12 carbon composite (Li 4.3 Ti 5 O 12 /C) with different carbon sources (polyacryl acid, polyvinyl alcohol, and carboxy methyl cellulose sodium). We have prepared the lithium excess Li 4.3 Ti 5 O 12 /C by a spray-drying method followed by calcining at 800°C in a nitrogen atmosphere. The TEM observations indicated that the surface of the Li 4.3 Ti 5 O 12 /C particle was clearly covered with an amorphous ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…Moreover, sucrose and glucose are generally used as carbon source in these works, which unfortunately cannot be used as binder. The dissoluble polymer, such as PVP, polyvinyl alcohol and polyacryl acid, is preferred to be used as binder and carbon source in spray drying method [40]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, sucrose and glucose are generally used as carbon source in these works, which unfortunately cannot be used as binder. The dissoluble polymer, such as PVP, polyvinyl alcohol and polyacryl acid, is preferred to be used as binder and carbon source in spray drying method [40]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of titanate or silicate electrode materials, the preparation of solutions is more difficult because few precursors are soluble in aqueous solutions of less-than-extreme pH. Chloride and/or alkoxide precursors (such as TEOS Si(OC 2 H 5 ) 4 [350,352], titanium isopropoxide Ti(OC 3 H 7 ) 4 [128,132,212,227,235,243,248,251] or tert-butoxide Ti(OC 4 H 9 ) 4 [211,222,229,238,239,240,241,249,250,265], …) can be solubilized in alcohol but hydrolysis takes place when mixing with water, leading to the precipitation of SiO 2 or TiO 2 unless special care is taken as in the strategies summarized in Figure 4.…”
Section: Formulation Of Solutions/suspensions: Inorganic Componentsmentioning
confidence: 99%
“…Common choices are polyethylene glycol (PEG), polyvinylalcohol (PVA) and polyvinylpyrrolidone (PVP) (see Table 4). PEG, PVA and PVP are of the non-ionic (steric) type but cationic additives are also reported (ammonium polycarboxylate [216,221], sodium carboxymethylcellulose [68,70,119,227,333], sodium dodecyl benzene sulfonate (SDBS) [53,65]).…”
Section: Formulation Of Solutions/suspensions: Organic/carbon Compmentioning
confidence: 99%
“…have observed that, under N 2 atmosphere, the chain‐stripping elimination of H 2 O is completed at 350°C while PVA is converted into an un‐saturated aliphatic polymer, which is further decomposed into a char at 700–800°C with about 4% carbon residue . Such a considerable carbon residual behavior have attracted much attention from various research fields, especially for some battery electrode materials with a low electronic conductivity, such as LiFePO 4 and Li 3 V 2 (PO 4 ) 3 because it can form a carbon coating on the particles of these phosphate materials and significantly improve their electrochemical performances. Besides, the formation of un‐saturated polymer intermediate product upon the elimination of H 2 O from PVA is favorable to produce more graphitic carbon due to the presence of conjugating ‐C=C‐C=C‐ carbon chains.…”
Section: Figurementioning
confidence: 99%